Isovitexin Inhibits Stemness and Induces Apoptosis in Hepatocellular Carcinoma SK-Hep-1 Spheroids by Upregulating miR-34a Expression - Xu, Chang; Cao, Xiaocheng; Cao, XiaoZheng; Liu, Lihua; Qiu, Yebei; Li, Xiang; Zhou, Lingli; Ning, Yingxia; Ren, Kaiqun; Cao, Jianguo (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: We previously demonstrated that isovitexin (apigenin-6-C-glucoside, ISOV) suppressed the stemness of human Hepatocellular Carcinoma (HCC) cells. However, the mechanism of its action remains to be deciphered. Objective: The current study was to examine whether ISOV regulates the miR-34a expression and hence suppresses the stemness of HCC SK-Hep-1 cells. Methods: After identification of the stemness, apoptosis resistance and decreased miR-34a expression of spheres from SK-Hep-1 cells (SK-SC), we utilized transfection of a miR-34a mimic or inhibitor to investigate the effects of ISOV on miR-34a, Bcl-2, Bax and Mcl-1 expression in order to understand the mechanism underlying ISOV-mediated repression of stemness and promotion of apoptosis. Results: Our results demonstrated that SK-SC displayed higher stemness and resistance to apoptosis, as well as reduced miR-34a levels compared to SK-Hep-1 cells. ISOV suppressed sphere and colony formation, and decreased CD44+ cell populations. In addition, ABCG2, ALDH1, and NANOG mRNA levels were decreased, while there was a concomitant increase in miR-34a levels. With regards to apoptosis-related proteins, ISOV increased Bax protein levels, and reduced Bcl-2 and Mcl-1 protein levels in SK-SC. Importantly, there was a cooperative effect when miR-34a was overexpressed in the presence of ISOV in SK-SC, and down-regulation of miR-34a attenuated the effects of ISOV in SK-Hep-1 cells. Conclusion: We suggest that ISOV-mediated miR-34a upregulation induces apoptosis and suppresses the stemness of SK-SC. Our data indicate that ISOV exhibits therapeutic potential for the treatment of HCC.
Keywords: miR-34a